Swertiamarin attenuates paraquat-induced pulmonary epithelial-like cell apoptosis via NOX4-mediated regulation of redox and mitochondrial function - Ji Wu; Yong Li; Xinju Li; Tao Wu (Universidade de São Paulo, 2023)
Abstract The aim of the present study was to investigate the effect of swertiamarin (STM) in attenuating paraquat (PQ)-induced human lung alveolar epithelial-like cell (A549) apoptosis and the underlying mechanisms. A549 cells were pretreated with different concentrations of STM for 2 hr and then cultured with or without PQ (700 μM) for 24 hr. Cell survival was determined using the CCK8 assay. Morphological changes, MDA content, inflammatory factors, fibrogenesis parameters, apoptosis rates, redox status and mitochondrial membrane potential (MMP) were evaluated. The expression of several genes involved in the modulation of redox status was measured by Western blotting. Cell viability and MMP were decreased, but the apoptosis rate and DCFH oxidation were elevated by PQ exposure. STM pretreatment notably increased cell viability and MMP and reduced the apoptosis rate and DCFH oxidation. Furthermore, TLR4- NOX4 signaling was significantly inhibited by STM. The downregulation of NOX4 by siRNA exerted the same protective effects as STM. This study provides the first evidence that STM attenuates PQ-induced pulmonary epithelial-like cell apoptosis via NOX4-mediated regulation of redox and mitochondrial function.